Build, operate and transfer (BOT) contract and its models from a Sharī‛ah perspective - Azman, Mohd Noor; Saidatol Akma, Mohd Yunus; Haron, Muhammad Nasir (Brill Academic Publisher, 2014)
The build, operate and transfer (BOT) contract is a new means of project and construction financing, which includes public-private partnership. Many countries are considering the BOT contract as a mode of financing for construction projects as all citizens need public infrastructure services. This article is an attempt to describe various modes, structures and arrangements of BOT and shed light on possible Sharī‛ah issues to demonstrate that BOT is a Sharī‛ah-compliant type of financing.